The Influence of Understanding Taxation and Tax Sanctions on MSME Taxpayer Compliance in Bengkong District - Siregar, Hanafi; Hati, Ravika Permata; Fauzi Yarlis, Yola (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to determine and analyze the influence of understanding taxation and tax sanctions on MSME taxpayer compliance in Bengkong District. The basic population of this research is micro, small, and medium enterprises in the Bengkong area. Sampling was carried out using a saturated sampling technique, in this study there were 85 micro, small, and medium business actors. Based on the results of the t-test, the tax understanding variable has a t count of 4.477 > t table 1.66365, the tax sanctions variable has a t count of 2.053 > t table 1.66365 showing that partially understanding taxation and tax sanctions have a positive and significant effect on mandatory compliance tax.